The roles of auxiliary players in health tourism industry in Penang, Malaysia - Che Omar, Che Musa; Tang, Kui Soo; Mansor, Nurwahidah (2013)
The main players of the drama in health tourism industry have always being acknowledgement said the medical service providers and health seeking tourists. Most of the credits have been directly taken by these groups. The success of health tourism industry in a location practically does rely on its supporting players in the industry’s supply chain. The objective of this paper is to introduce the critical roles played by the supporting activities in the health tourism industry. In addition, it is also to facilitate the formulation of recommended interventions to develop the competitiveness of each of the identified roles the players. The Value Chain Analysis (VCA) will be applied in this research paper as a methodology for the systematic competitiveness analysis of enterprises and local industries. All relevant activities and processes will be examined and sorted out which have a critical relevance to improve the competitiveness in health tourism industry. The application of VCA in the health tourism industry has a clear objective in mind that is to introduce roles of processes and elements in the production of health tourism services of the supporting players. The importance of VCA is also indicates the critical phase in the process of producing best services. Details observation will also be conducted with the local entrepreneurs in Penang, as chosen to be the case study of this research paper. Initial findings show that the local entrepreneurs in Penang are adapting well to compete in the industry and being innovative in different ways.